Psychiatry and Bureaucratic Obstacles in Non-western and Western Countries - Steinmetz, Carl Hermann Dino; Pal, Mahendra (Advances in Social Sciences Research Journal, 2026)
This article examines the role of bureaucratic structures in psychiatry and psychology across Western and non-Western contexts, with a particular focus on how legal, institutional, and cultural factors shape access to mental healthcare. Drawing on empirical insights from intercultural psychiatric practice in the Netherlands and a detailed institutional analysis of India, the study conceptualises mental health systems as complex configurations of medical, administrative, and socio-legal arrangements rather than purely clinical entities. The analysis demonstrates that bureaucratic obstacles emerge through multiple mechanisms, including regulatory frameworks, professional licensing systems, fragmented service provision, and funding structures. In non-Western contexts, these challenges are further compounded by cultural stigma, plural medical traditions, and collective decision-making norms. Using India as a case study, the article traces the historical evolution of psychiatric bureaucracy from colonial asylum systems to contemporary rights-based governance under the Mental Healthcare Act (2017), highlighting the coexistence of biomedical and traditional systems within a dual-track administrative model. The article argues that mental health outcomes cannot be understood without considering the interaction between bureaucracy, culture, and broader social determinants such as education, employment, and social inclusion. It further presents intercultural, socially embedded models of care as a promising alternative to standardised bureaucratic approaches. The study concludes that improving mental healthcare requires not only clinical innovation but also institutional reform, cultural competence, and the reduction of bureaucratic barriers, particularly for migrant and marginalised populations.